Bilangan Kromatik Graceful Pada Keluarga Graf Grid - Arika Indah Kristiana; Anzori Anzori; Robiatul Adawiyah; Slamin Slamin; Ermita Rizki Albirri (Universitas Islam Jember, 2023)
All graph in this paper be a connected and simple graph. Let c:V(G)→1,2,…,k is a proper vertex coloring where k ≥ 2 which induces a proper edge coloring c':E(G)→1,2,…,k define by c' (uv)=|c(u)-c(v)|, where uv in E(G) is called graceful k-coloring. A vertex coloring c of graph G is a graceful coloring if c is a graceful k-coloring for some k∈ N. The minimum k for which a graph G is a graceful chromatic number denoted by χ_g (G). In this paper, we will investigate the establish exact value of graceful chromatic number on grid graph family namely H graph 〖(H〗_n) for n≥2 and grid graph for m,n≥3. Keywords: graceful coloring, graceful chromatic number, grid graph family